The Baseline Serum Homocysteine Levels in Peri- and Postmenopausal Women - Kıran, Hakan; Kıran, Gürkan; Kaplanoğlu, Mustafa; Köstü, Bülent; Çetin, Turan (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: To investigate the effects of perimenopause, natural menopause and surgical menopause on the baseline serum homocysteine (Hcy) levels. STUDY DESIGN: The baseline serum Hcy levels were measured in 33 perimenopausal and 153 postmenopausal women and were compared between groups RESULTS: The mean Hcy levels of perimenopausal (n=33) , natural menopausal (n=99) and surgical menopausal (n=54) women were 12,3 μmol/L, 13,4 μmol/L and 13,2 μmol/L, respectively. There were no statistically significant differences in the baseline levels of Hcy between the study groups (p=0.73). CONCLUSIONS: The baseline Hcy levels of postmenopausal women were not higher than perimenopausal women. On the other hand, there were no significant differences in the baseline Hcy levels between the natural and surgical menopausal groups.